The Kidney Transplant Equity Index: Improving Racial and Ethnic Minority Access to Transplantation. Issue 3 (28th September 2022) - Delman, Aaron M.; Turner, Kevin M.; Silski, Latifa S.; Quillin, Ralph C.; Estrada, Martha; Lemon, Kristina; Cuffy, Madison C.; Shah, Shimul A.
Abstract : Objectives: To develop a scalable metric which quantifies kidney transplant (KT) centers' performance providing equitable access to KT for minority patients, based on the individualized prelisting prevalence of end-stage renal disease (ESRD). Background: Racial and ethnic disparities for access to transplant in patients with ESRD are well described; however, variation in care among KT centers remains unknown. Furthermore, no mechanism exists that quantifies how well a KT center provides equitable access to KT for minority patients with ESRD. Methods: From 2013 to 2018, custom datasets from the United States Renal Data System and United Network for Organ Sharing were merged to calculate the Kidney Transplant Equity Index (KTEI), defined as the number of minority patients transplanted at a center relative to the prevalence of minority patients with ESRD in each center's health service area. Markers of socioeconomic status and recipient outcomes were compared between high and low KTEI centers. Results: A total of 249 transplant centers performed 111, 959 KTs relative to 475, 914 nontransplanted patients with ESRD. High KTEI centers performed more KTs for Black (105.5 vs 24, P <0.001), Hispanic (55.5 vs 7, P <0.001), and American Indian (1.0 vs 0.0, P <0.001) patients than low KTEI centers. In addition, high KTEI centers transplanted more patients with higher unemployment (52 vs 44, P <0.001), worse social deprivation (53 vs 46, P <0.001), and lower educational attainment (52 vs 43, P <0.001). While providing increased access to transplant for minority and low socioeconomic status populations, high KTEI centers had improved patient survival (hazard ratio: 0.86, 95% confidence interval: 0.77–0.95). Conclusions: The KTEI is the first metric to quantify minority access to KT incorporating the prelisting ESRD prevalence individualized to transplant centers. KTEIs uncover significant national variation in transplant practices and identify highly equitable centers. This novel metric should be used to disseminate best practices for minority and low socioeconomic patients with ESRD.